Identification of Adverse Drug Reaction Incidents in Statin Use in Depok Hospital Inpatient - Nurhikmah, Rizky; Andrajati, Retnosari; Sari, Santi Purna (Green Publisher Indonesia, 2025)
One of the adverse drug reactions that occur in patients who receive treatment therapy is drug side effects. Statins are the first choice in cholesterol-lowering therapy. Although statins are safe and well tolerated, they have the potential for side effects. The purpose of this study is to determine the prevalence of adverse drug reactions, the incidence of adverse drug reactions that occur, and the probability score of adverse drug reactions based on the Naranjo Algorithm instrument in patients with inpatient atherosclerosis cardiovascular disease who use statin therapy at RSUI. The method used in this study is a prospective observational descriptive method with observation through patient interviews and medical record data collection as well as causality analysis using the Naranjo Algorithm. The results of this study were obtained from 116 patients who used statin therapy in the RSUI inpatient room in accordance with the inclusion and exclusion criteria. Of the 116 patients, as many as 14 patients (12.07%) experienced adverse drug reactions statins. Adverse drug reactions felt included shoulder pain (3.40%), nausea (2.60%), muscle pain (1.70%), blurred vision, difficulty sleeping, chest palpitations, joint pain, dizziness and body aches as much as 0.9% each. The total probability score of the Naranjo algorithm is a probable score of 5-8 in 7 patients (50%) and a possible score of 1-4 (50%).